A study on annealing‐induced softening in cold drawn Cu−Cr−Sn alloy: Weichglühen einer kaltgezogenen Cu−Cr−Sn‐Legierung. Issue 11 (26th October 2018) - Luo, Z.; Luo, F.; Xie, W.; Chen, H.; Wang, H.; Yang, B.
Abstract: The softening behavior of a 60 % cold‐drawn Cu‐0.48Cr‐0.16Sn alloy during annealing at temperatures between 450 °C and 750 °C was investigated. The mechanical properties and microstructures evolution of the alloy in both as‐drawn and annealed conditions were analyzed using hardness measurement, transmission electron microscopy (TEM) and electron back‐scatter diffraction (EBSD) technique. The results showed that the softening behavior of the alloy was strongly affected by precipitate coarsening, recovery and recrystallization, and was predominant by recrystallization when the temperature higher than 500 °C. The recrystallization kinetics was characterized by measurements of hardness. The obtained experimental data were evaluated in terms of the Johnson‐Mehl‐Avrami‐Kolmogorov model. The values of the Avrami exponent were ranged from 0.87 to 1.36, and the activation energy of recrystallization was about 117.9 kJ mol ‐1 for 60 % cold‐drawn Cu−0.48Cr−0.16Sn alloy, which suggested that recrystallization process of the Cu−Cr−Sn alloy was mainly controlled by grain boundary migration. The softening resistance of the Cu−Cr−Sn alloy is stronger than that of the pure copper due to the addition of Chromium (Cr) and Tin (Sn). In addition, the reduction in strain had a positive effect on the improvement of softening resistance.